تأثير الرياح على أمواج البحر في شاطئ اللاذقية - الأعرج بدر; إبراهيم بهجت (Latakia University Journal -Basic Sciences Series, 2018)
There are many reasons for developing our knowledge of the marine sciences. First because of their importance as sources of food, chemicals and power. They are exploited to a very minor degree. On the other hand, oceans and sea are still a vital important avenue of transportation. They form a sink into which industrial waste (radioactive waste) is dumped. Our basic goal of sea waves and wind is to obtain a clear and systematic description of the direction which such wastes may follow. This work aims at analyzing wave and wind data for Lattakia coast. We obtained some important results, which are hereby tabulated from three months measurements in this field. The analysis of the data showed that the most severe wave storms occurred in December 2002 at Lattakia Coast. توجد أسباب عديدة لتطوير معرفتنا في مجال علوم البحار, لكونها مصادر هامة للأغذية, والمواد الكيميائية والطاقة...الخ. ولقد استثمرت هذه المصادر بدرجة قليلة حتى وقتنا الحاضر. علاوة على ذلك, تعتبر المحيطات والبحار بيئة حيوية هامة في عمليات النقل المختلفة. بالنسبة إلى الدول الصناعية الكبرى تشكل المحيطات والبحار أحواض ومستودعات للتخلص من النفايات الصناعية (النفايات ذات النشاط الإشعاعي). ويكمن هدفنا الأساسي في دراسة الأمواج وتأثير الرياح عليها للحصول على وصف واضح متناسق لاتجاه حركة الرياح الأمواج التي تحمل النفايات وفق اتجاه حركتها. يهدف هذا العمل لتحليل معطيات الأمواج والرياح في شاطئ اللاذقية. ومن خلال دراستنا وأبحاثنا المستمرة لمدة ثلاثة أشهر في هذا المجال حصلنا على بعض النتائج الهامة والتي تم عرضها في هذه النشرة. وقد بينت القياسات أن اشد العواصف التموجية في شاطىء اللاذقية حصلت في شهر كانون الأول لعام 2002.